Use of lectins as vector molecules for delivery of drugs to cells and tissues. Report 2. - Antonyuk, V.O.; Skorohyd, N.R.; Lozynskyi, A.V.; Antonyuk, R.V.; Lesyk, R.B.; Stoika, R.S. (Вiopolymers and Cell, 2019)
Aim.To determine cytotoxic effects towards a tumor cells culture of the heterocyclic derivative conjugated with lectins of different carbohydrate specificity. Methods. Conjugation of lectins (Pea seeds (PSA), peanuts (PNA) and erythroagglyutinin from bean seeds (PHA-E) with thiopyrano[2,3-d]thiazole Les-1895, biotesting these conjugates in the cell culture. Results. The conjugates of Les-1895 with specific lectins posses increased cytotoxic effects towards Jurkat cells — by 23 % for PSA-Les-1895, 34 % for PNA-Les-1895, and by 12 % for PHA-E-Les-1895. IC50 of Les-1895 conjugates was ≈ 10 μg/ml, whereas at using free Les-1895 – it was ≈ 30 μg/ml. The PNA and PHA-E conjugates with Les-1895 suppressed the viability of HCT 116 cells more considerably than the PSA conjugate. A cytotoxic action of PNA (IC50 = 4 μg/ml) and PHA-E (IC50 = 3 μg/ml) conjugates was more pronounced than the effect of free Les-1895 (IC50 = 10 μg/ml) or intact lectins. The conjugation of Les-1895 with human serum albumin (HSA) increased the water solubility, however, such conjugation decreased the cytotoxic effect towards Jurkat cells by 40 %. The pseudonormal cells line HEK 293 was less sensitive to the action of native lectins — PSA, PNA and PHA-E as well as to the action of conjugates of these lectins. Conclusions. Conjugation of Les-1895 with specific lectins enhanced a cytotoxic effect. The obtained results suggest a possibility of the addresed delivery of biologically active compounds to specific cells of tissues and organs of the human body.